The Role of Purba Bolon House Architecture in Social Structure and Kinship - Monica Uli Batubara; Immanuel Silaban; Cristien Oktaviani Saragih; Dony Sigiro; Basri Natan Sitanggang; Putri Hutabarat (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Traditional houses are one of the cultural heritages left by ancestors and are now part of local wisdom, especially in the Batak Simalungun area. The Ancient Bolon House is a traditional house typical of the Simalungun people which functions as a symbol of identity and reflects the cultural values of the Batak Simalungun people. This study aims to describe the function of each part of the Ancient Bolon House using qualitative research methods. In collecting data, this study uses literature study techniques by looking at various sources such as books, journals, and websites related to the Ancient Bolon House. The results of the study show that the Ancient Bolon House has several main parts, each of which has its own function and meaning, and contains important cultural values to be preserved by the younger generation through wedding activities and customs in family events. The Ancient Bolon House can also be a tourist attraction for foreign visits with its own cultural story.